Assessment of Myometrial Concentrations of Oestrogen and Progesterone Receptors in the Lower Uterine Segment of Full-Term Pregnancies in Presence or Absence of Labour - Joana Soares de Arruda; Edward Araujo Júnior; Manuel de Jesus Simões; Luiz Kulay Júnior (Journal of Pregnancy)
Objective. To assess the concentration of progesterone (PRs) and oestrogen (ORs) receptors of myometrium of full-term pregnant women in the myometrium of lower segment of the uterus in relationship with presence or absence of labour. Methods. This was a cross-sectional prospective study with 21 pregnant women, being 6 in labour (Group I) and 15 without labour (Group II). The biopsy of myometrium was realized during caesarian section, and the excised tissue was stained using immunohistochemical techniques for the quantification of the receptors, and with the aid of image-analysis software, the numbers of receptors for each hormone were determined spectrophotometrically. The Mann-Whitney test was used to compare the pregnant women in each study group with respect to the numbers of ORs and PRs. The Wilcoxon test was used to compare the concentration of ORs and PRs in each group separately. Results. The mean of gestational age was 39 weeks, (range, 37 to 41 weeks). The medians of PRs and ORs in pregnant women in labour (Group I) were 29.3 (range, 24.6–30.2) and 32.3 (range, 22.9–49.0), respectively. The medians of PRs and ORs in pregnant women without labour (Group II) were 43.6 (range, 23.6–70) and 43.9 (range, 18.3–62.6), respectively. We did not observe significant differences of the number of ORs and PRs in both groups ( and 0.37, resp.). The number of ORs was statistically more than that of PRs in Group II (Z calculated = 16.00). Conclusion. The concentrations of PRs and ORs were similar in the myometrium of the lower uterine segment of pregnant women during and without labour, but the concentration of ORs was more than that of PRs in the myometrium of the lower uterine segment of pregnant women without labour.